Analysis of pharmaceutical workers recommendations for wound-healing drugs in ukraine - Arsenii Kondratskyi; Olena Glushchenko; Tetiana Butkevych (Bogomolets National Medical University, 2021)
The occurrence of superficial wounds remains one of the most significant problems all the time among different types of household injuries. Up to 40 % persons annually have such damages of the skin like abrasions, scratches, cracks, suppurations, cuts, bedsores, and others. The problem of choosing a suitable drug arises acutely, since most pharmacists consider the issue of treatment by themselves. Patient's referral to hospital departments for doctors advise remains minimal. Pharmacy specialists carry out pharmaceutical care and perform a personal analysis due to the given initial information about the mechanism, place of occur, size of wound and stage of the process of wound healing. Considering previous experience in fulfilling customer needs, they select optimal remedy, determine the majority of choice and thus, may be identified as the sales leaders. As for January 2021, the range of topical drugs used for the treatment of wounds numbered 270 trade names according to the State registry of medicines of Ukraine. They included 62 types of active pharmaceutical ingredients. Antimicrobial (antiseptic), anti-inflammatory, decongestant, protective and emollient action properties are underlined in their pharmaceutical inserts. It is similar for most of the medicines that are available on the Ukrainian pharmaceutical market. After all, their effectiveness to satisfy a patient need is as different as the price point. The choice of the optimal in composition and rational in the dosage form causes certain difficulties among the available wide range of medicines. Registrated semi-solid wound-healing drugs are represented by three groups of ATC classification: D03 - drugs for wounds and ulcers, D06 - antibiotics and chemotherapeutic drugs for use in dermatology, D08 - antiseptic and disinfectant drugs (table 1). Ointments predominate among semi-solid dosage forms with range 67.3 %, creams  -26.5 %, gels - 10.2 %, liniments - 6.1 %, and jellies only 2.0 % of the market. 59.2 % of semi-solid wound-healing drugs are produced by domestic enterprises, and 40.8 % - by foreign manufacturers. The recommendations for the use of semi-solid drugs were distributed as follows: for the first phase of wound process - 48.9 %, for the first and second phases - 12.2 %, for the second phase - 10.2 %, for the second and third phases - 26.4 %, for the third phase - 2.0 %. The article summarizes the results of a questionnaire of pharmaceutical specialists on the available and free sale wound-healing medicines among registered on the Ukrainian market, that are most promoted and recommended. The purpose of our work was to single out available and free sale wound-healing medicines among registered on the Ukrainian market, that are most promoted and recommended by pharmaceutical specialists. This would help to highlight the real picture of sales, to analyze the components of leading products and, as a result of additional research, to propose a model for the complex pharmaceutical development of a new wound-healing medicine in a rational dosage form with safe and effective active ingredients of plant origin, and, consequently, competitive for pharmaceutical manufacturers. The list of registered medicines was composed in accordance with the data from the State Register of Medicines of Ukraine (registrated trade names). The total number of respondents was 176. Questionnaire survey was the main method of information's collecting: 46 respondents were interviewed individually, 130 persons of the target audience - by electronic form. Questionnaire contained the same questions for the individual survey and online one. Questionnaire contained particular situational tasks and questions related to the practical experience of the pharmaceutical specialists: 12 questions, among which 5 questions provided an answer in detail. Whole data was analyzed systematically and statistically. 342 reviews on 36 medicines trade names were received while answering the question about the drug's recommendation for quick healing of abrasions and scratches. Various drugs promoting rapid injury healing («Bepanten®» ointment, «Levomekol» ointment, «Pantestin-Darnitsa®» gel and «Riativnyk®» cream) determined in the most mentioned requests. We found out that most pharmaceutical specialists chose semi-solid dosage forms containing dexpanthenol for light burn wounds healing («Bepanten®» cream and ointment, «D-panthenol», «Pantecream», «Pantexol-Jadran», «HepiDerm-Zdorovye»). Pharmaceutical specialists recommend «Contractubex®» and «Solcoseryl» mostly to improve wound healing and minimizing the development of a cosmetic scar. Only 1/3 of respondents would recommend to a pharmacy visitor to exam skin defect by doctor or cosmetician and get reliable advice. The recommendations of pharmaceutical specialists for shallow cuts were predominantly determined by antiseptic drugs - most of them chose iodine solutions. 264 reviews were received for 32 trade names of medicines as effective treatment for bedsores. Respondents preferred zinc oxide preparations usage. According to the investigation, the opinions of the interviewed pharmaceutical specialists were focused on the semi-solid dosage forms (ointments, creams etc) for various wound care (abrasions and scratches, burns, scars, bedsores). Dosage forms of medicines for the treatment of cut wounds were an exception. Solutions and new kind of plasters - Skin glue, were the drugs of choice in this group. Phytomedicines practically did not appear among the respondents answers.